PENDIDIKAN KESEHATAN TENTANG KEGAWATDARURATAN PREEKLAMSIA PADA IBU HAMIL TRIMESTER III DI KLINIK FATIMAH ALI MEDAN - Purwaningsih, Purwaningsih; Nina Fentiana,; Arni Juwita,; Nisrina, Nisrina; Gita Agnes, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
Pregnancy is a physiological stage that causes significant changes in various body systems, potentially affecting the health conditions of both mother and fetus. During pregnancy, women often experience a variety of changes including physical symptoms, body image changes, concerns about fetal well-being, adjustments to lifestyle changes, emotional disorders, as well as anxiety related to pregnancy, labor, and birth. Preeclampsia is a condition of increased blood pressure found in pregnant women. This condition is one form of pregnancy emergency that risks not only to the mother and the fetus if it does not get proper treatment. Preeclampsia is an increase in blood pressure that only arises after pregnancy reaches 20 weeks, and accompanied by the rapid increase in maternal weight due to swelling and in laboratory examination found protein in urine (proteinuria). The earliest symptoms often found in pregnant women with preeclampsia are the occurrence of drastic weight gain at a rapid time, which causes the occurrence of odem on the face and extemity. Edema that is common in pregnant women is considered common and common, but this should be considered as a sign of pre-eclampsion, so that it is necessary to provide health education to pregnant women to always check their pregnancy to the nearest health care. This community devotion aims to improve the knowledge of pregnant women to understand early about the health of preeclampsi emergency and signs of preeclampsi symptoms and prevention so that pregnant women expect to understand early in pregnancy. The method used in devotion to this community is to provide health education about preeclampsi emergencies in pregnant women trimester III at Fatimah Ali Medan clinic